The Implementation of CLT in EFL Classroom - Kalayo Hasibuan (English Instruction, 2021)
One approach that can be used in teaching English is Communicative Language Teaching (CLT). CLT has been widely implemented in several EFL classes. CLT can also be implemented in schools that use the 2013 curriculum. Implementation of CLT can help learners to be more active in learning and able to communicate competently. In implementing CLT, there are several obstacles faced by teachers or students such as teaching models, teaching materials, student participation and eavaluation. However, these obstacles can be overcome by the way teachers can understand what CLT is and apply creative language learning methods.